A Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Mengikuti Uji Sertifikasi Teknisi Akuntansi - Izzul Muttaqin; Kusumawati , Fariyana (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
The focus of this research is to examine whether there is an influence of quality motivation, motivation to take the accounting technician certification test cluster for preparing financial statements based on SAK ETAP, career motivation and economic motivation on accounting students' interest in taking the accounting technician certification.This type of research is quantitative with multiple linear regression analysis using SPSS version 25. Active students of S1 Accounting Study Program, Faculty of Economics and Business, Trunojoyo University Madura became the population in this study. The sample in this study were some active students of S1 Accounting Study Program in the fifth semester and above with a sample size that could be used in the study were 100 respondents. Sampling using purposive sampling, namely sample collection selected with certain criteria. Data obtained through questionnaires using a Likert scale. The test results in this study concluded: The interest of accounting students in taking the TA certification test is not significantly influenced by the quality and career motivation variables. While the motivation to take the SAK ETAP TA test and economic motivation have a significant influence on the interest of accounting students in taking the TA certification test. Keywords: quality motivation; motivation to take the SAK ETAP TA test; career motivation; economic motivation; student interest in taking the accountant technician certification test.